The 1921 Constitution of Georgia: A Symbol of the Independence of Georgia - Malkhaz Matsaberidze (Journal of Constitutional Law, 2021)
The founders of the Democratic Republic of Georgia (1918-1921) considered the drafting of the basic law of the country, the Constitution, to be particularly important and saw its adoption as the most significant event after the Declaration of Independence. The Constituent Assembly of Georgia (1919-1921) drafted and adopted the Georgian Constitution on 21 February 1921, which holds its honorable place in the history of world constitutionalism. It is based on two basic principles – the freedom of the nation and the freedom of an individual. The Constitution provided solid foundation for the development of the Georgian state with its coherent democratism. In Soviet times, the 1921 Constitution was a symbol of what the Georgian State should have been like. And after the restoration of independence, it was indisputable, that the 1921 Constitution had to serve as the basis for the new constitution of the country.